Mobile Internet Analysis in Prevention of Negative Impacts of Information and Communication Technology in Indonesia - Nauvaldi, Muhamad Rio (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
The development of information technology's development can create a global world and create space for a new life in society, namely the life of a virtual community. However, it cannot be denied that not all internet activities are always positive. However, the internet also has a negative side, so it is necessary to find more effective and preventive ways of dealing with the negative impacts of information technology. The aims of this research are: 1) To find out the negative impact of mobile internet usage in Indonesia. 2) To find out how the law prevents the negative impact of information technology in Indonesia. 3) To find out the sanctions that will be given and the regulations that can be used to ensnare perpetrators of mobile internet irregularities in Indonesia. This study uses a normative juridical approach, and the method used is qualitative. The data sources taken in this study consist of primary, secondary and tertiary. Data analysis was carried out by analyzing and describing the data collected to make a research conclusion and using a field approach, namely by examining internet crime cases so that this research can be obtained a conclusion as an answer to the problems discussed in this study.